Donor–Acceptor Interactions Induced Interfacial Synthesis of an Ultrathin Fluoric 2D Polymer by Photochemical [2+2] Cycloaddition. Issue 11 (18th January 2021) - Sun, Qingzhu; Pan, Qingyan; Ban, Yanqi; Liu, Hui; Fan, Chunyan; Sun, Lishui; Zhao, Yingjie
Abstract: Invited for the cover of this issue is the group of Prof. Dr. Yingjie Zhao at Qingdao University of Science and Technology. The image depicts the ultrathin two‐dimensional polymer reported in this work. Read the full text of the article at 10.1002/chem.202004797 . Abstract : " In this study, we successfully prepared a crystalline ultrathin two‐dimensional polymers (2DPs) film at the air/water interface through [2+2] photo‐cycloaddition. In addition, the molecular structure of the 2DP was explicitly analyzed by a combination of SAED pattern and molecular‐mechanics‐based structural simulation ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 3661 ff. (DOI: 10.1002/chem.202004797 ).